How do complementarity and discount choices interact with latitude of price acceptance in price bundling?. Issue 7 (4th September 2019) - Saini, Gordhan K.; Sahay, Arvind; Kalyanaram, Gurumurthy
Abstract : Purpose: This paper aims to examine three important questions: What would be the effects of pricing at the lower end of a wide vs narrow latitude of price acceptance (LPA) on consumer choice of the bundle? How would the nature of a bundle frame (i.e. discount on bundle vs discount on components) and discount frame (i.e. discount as absolute off vs discount as percentage off) influence the preference given to a price level that is at the wide or narrow end of the LPA? Would the effect be significantly different if the bundle components were complementary vs if they were non-complementary? Design/methodology/approach: The authors carried out two studies using between-subject experimental design. In Study 1, the authors used 2 (LPA: wide/narrow) × 2 (complementarity: yes/no) × 2 (bundle frame: together/separate) design, and in Study 2, the authors replaced bundle frame with discount frame (i.e. absolute off/percentage off). Findings: The authors find that the LPA effect is likely to outweigh the complementarity effect; however, a combined effect of complementarity and bundle frame is stronger than the LPA effect. Also, for a wide (narrow) LPA product bundle, absolute off (percentage off) discount frame is more attractive. Practical implications: Managers should use bundling strategy with complementary products having wider LPA. In case of wide LPA and complementary products, both together and separate frame could be the best bundling strategy while in case of narrow LPA and complementary products, together frame could be the best bundling strategy. Originality/value: The main contribution relates to the role LPA plays in consumer evaluation of a bundle offer and its interaction with complementarity and discount frame. The authors apply the range hypothesis principles (i.e. price-attractiveness judgments are based on a comparison of market prices to the endpoints of a range of evoked prices) in the bundling context and extend the earlier work in the area of complementarity and discount frame.